2011
DOI: 10.5005/jp-journals-10001-1056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blind Nasal Packing vs Endoscopic Control of Epistaxis in an Emergency Setting

Abstract: Aim: To compare the precision and efficacy of endoscopic control versus nasal packing in epistaxis presenting to the emergency room.Design: Open labelled randomized controlled trial for comparison of precision and efficacy of emergency blind nasal packing with primary endoscopic control of epistaxis.Subjects: A total of 160 consecutive patients of epistaxis in the age group of 40 to 70 years were randomized in two groups (A and B) of 80 patients each. Group A was subjected to blind nasal packing and group B to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…This technique can cause some problems such as pain and discomfort, septum necrosis, local infection, toxic shock syndrome, and the need for using antibiotics or analgesics. Some of these can cause irreversible and dangerous side effects [5,6]. Although in this study, all these side effects were not seen in the hospital or patients' follow up, some side effects such as intolerance and nausea were significantly more in ANP group.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…This technique can cause some problems such as pain and discomfort, septum necrosis, local infection, toxic shock syndrome, and the need for using antibiotics or analgesics. Some of these can cause irreversible and dangerous side effects [5,6]. Although in this study, all these side effects were not seen in the hospital or patients' follow up, some side effects such as intolerance and nausea were significantly more in ANP group.…”
Section: Discussioncontrasting
confidence: 55%
“…These nonsurgical procedures are preferred to control mild-to-moderate bleedings [27]. Using these methods, due to their convenience and less pain, are increasing in comparison to painful surgical methods and chemical cauterization [6]. In the present study, NG group showed lower pain during the procedure and higher patients' satisfaction in comparison to ANP group.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…With the advent of nasal endoscope, the diagnosis and treatment of epistaxis became easy. Nasal endoscope has superior lighting quality and magnification which give a detailed view of the nasal cavity and the covert areas of the nose situated in the deep crevices of the lateral nasal wall [5][6][7].…”
Section: Introductionmentioning
confidence: 99%